The Influence of Motivation and Work Discipline on Employee Performance: Study of One of The Pharmaceutical Health Equipment Companies in Bandung City - Fauziah Nur Hasanah; Dhea Perdana Coenraad; Lungguh Jatmika; Rd Rahadian Arby (Majalah Bisnis & IPTEK, 2024)
This study aims to determine the extent to which work motivation and discipline impact the performance of employees at a pharmaceutical medical equipment company located in Bandung City. The research method employed is descriptive and verification techniques. The researchers employed a data collection strategy involving the distribution of a questionnaire to a sample size of 40 individuals. The instrument underwent rigorous testing before its deployment to ensure its validity and reliability. The statistical technique employed was path analysis, conducted using SPSS version 25 software. The results of descriptive research conducted at a pharmaceutical medical equipment company in Bandung revealed that motivation was evaluated. The work discipline is commendable, and the employee performance is excellent. The verification results indicate that Motivation and Work Discipline significantly impact the performance of study employees at a pharmaceutical medical equipment company in Bandung City. Additionally, there is a correlation between Work Motivation, Work Discipline, and the performance of study employees at the same company.